Analisis Peran Kearifan Lokal dalam Meningkatkan Daya Tarik Wisata Budaya dan Ekonomi Kreatif - Amelia, Nur Amelia; Ellia, Adinda Putri; Putri, Hesti Amelia; Ridho, Ichsan Anta; Zora, Fera (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to deeply investigate the role of local wisdom in enhancing the attractiveness of cultural tourism and promoting the growth of the creative economy. This study employs a qualitative approach with literature review as the primary data collection technique. Data is collected from various secondary sources such as scientific journals, books, research reports, policy documents, and related articles relevant to the topics of local wisdom, cultural tourism, and the creative economy. The obtained data is then analyzed descriptively qualitatively to identify key themes, patterns of interrelation, and the strategic implications of utilizing local wisdom in the development of tourism and the creative economy. The analysis results show that local wisdom has significant potential in creating authentic cultural tourism experiences and enhancing the added value of creative economy products. This directly contributes to the development of sustainable tourism and economies. Additionally, this study also identifies various challenges, such as cultural commercialization and the capacity limitations of local communities, as well as opportunities like policy support and strategic partnerships, in optimizing the role of local wisdom in both sectors